2013
DOI: 10.1021/ie402148u
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecule Sorption and Diffusion in HEMA/MAA Hydrogels

Abstract: Transient solute absorption and desorption concentration profiles were measured in a 70 wt % hydroxyethyl methacrylate (HEMA)/30 wt % methacrylic acid (MAA) anionic hydrogel using two-photon confocal microscopy. Dilute aqueous solutes included fluorescently labeled dextrans with molecular masses of 4, 10, and 20 kDa, and fluorescently labeled cationic avidin protein. Cross-linking densities with ethylene glycol dimethacrylate (EGDMA) varied from 0 to 1 wt % with polymer volume fractions increasing from 0.15 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
114
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(118 citation statements)
references
References 79 publications
(218 reference statements)
4
114
0
Order By: Relevance
“…Besides, the effective-medium theory underestimates the dynamic drag and obstruction of small solutes, (Liu et al, 2013) i.e. solutes smaller than the average mesh size, which is the case of the studied drugs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Besides, the effective-medium theory underestimates the dynamic drag and obstruction of small solutes, (Liu et al, 2013) i.e. solutes smaller than the average mesh size, which is the case of the studied drugs.…”
Section: Discussionmentioning
confidence: 97%
“…Liu et al (Liu et al, 2013) studied the diffusion of dextrans with molecular masses of 4, 10, and 20 kDa and the cationic avidin protein in a HEMA/MAA (70/30,w/w) anionic hydrogel. They found that for dextrans, although being size excluded, the measured diffusivities were in good agreement with those predicted from a new effective-medium model which considered solute transport only in the accessible liquid-filled voids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PMAA is one of the most typical pH-responsive polymers used as the carriers for drug delivery system which can achieve the precise targeted drug release. It has been widely applied in biomedical applications, [40] coatings, [41] and sensors. [42] Inspired by the previous work, we designed and synthesized novel hybrid silica nanoparticles grafted with photoand pH-sensitive random copolymer P(SPMA-co-MAA) by SI-ATRP.…”
Section: Preparation Of Monodispersed Snps(sio 2 )By Stöber Methodsmentioning
confidence: 99%